TRADITIONAL BATAK MUSIC IN THE CONTEXT OF WORSHIP: CASE STUDY OF MANAGEMENT AND THE ROLE OF MUSICIANS - Victor Martin Tama Lucky Situmorang; Mauly Purba; Pulumun B Ginting (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
When hearing traditional music presented as accompaniment to worship, the author has a desire to know how much church management has put into preparing the presentation of music to accompany worship, as well as the role of musicians in delivering the worship musically. The aims of this research are to find out 1) how the presentation of Batak cultural worship is managed using traditional music, 2) to find out the role of musicians as accompanists of worship. The type of research used in this research is qualitative research with a descriptive approach. This research was conducted at the HKBP Pardamean church. The selection of research samples was based on the researcher's initial observations, where the researcher saw the phenomenon of presenting traditional music performances in the context of worship with various church management that were different from each other. Then the researchers also saw the phenomenon of the role of musicians who present worship music in services at the HKBP Pardamean Church. HKBP Pardamean holds a Cultural Service once a month as an effort to exist "Batak" in the context of presenting worship. At HKBP Pardamean, a presentation of worship is carried out by management. HKBP Pardamean holds a Cultural Service once a month as an effort to exist "Batak" in the context of presenting worship. Where nowadays it is almost eroded by the current of globalization. One of the symbols of culture that has begun to disappear from the Batak identity itself is traditional music.